To find the change in height of the parasail, we need to calculate the difference between the starting height and the ending height.
- Initial height = \( \frac{1}{20} \) meter
- Final height = \( \frac{1}{50} \) meter
We can convert both fractions to a common denominator to make the subtraction easier. The least common multiple of 20 and 50 is 100.
Now, let's convert both fractions:
\[ \frac{1}{20} = \frac{5}{100} \]
\[ \frac{1}{50} = \frac{2}{100} \]
Now we can calculate the change in height:
\[ \text{Change in height} = \text{Initial height} - \text{Final height} \]
\[ \text{Change in height} = \frac{5}{100} - \frac{2}{100} = \frac{3}{100} \]
Thus, the change in height is \( \frac{3}{100} \) meter.
The correct response is:
\( \frac{3}{100} \) meter.